The effect of wheelchair propulsion style on changes in time spent in extreme wrist orientations after a bout of fatiguing propulsion. Issue 10 (3rd October 2017) - Zukowski, Lisa A.; Hass, Chris J.; Shechtman, Orit; Christou, Evangelos A.; Tillman, Mark D.
Abstract: This study compared how wheelchair propulsion styles affect changes in percentage of time spent in extreme wrist orientations, which have been associated with median nerve injury, after a fatiguing bout of propulsion. Twenty novice, non-disabled adult males learned arcing (ARC) and semicircular (SEMI) propulsion styles and utilised each to perform a wheelchair fatigue protocol. ARC and SEMI did not significantly differ in terms of changes after the fatigue protocol in percentage of time spent in extreme flexion/extension or radial/ulnar deviation at the push phase beginning or end. A pattern was observed, although not significant, of greater increases in percentage of time spent in extreme wrist extension and ulnar deviation during the push phase beginning and ulnar deviation during the push phase end while utilising SEMI relative to ARC. This study evinces that individual differences are greater than observed changes in extreme wrist orientations for both propulsion styles. Practitioner Summary: How wheelchair propulsion styles change with fatigue in terms of extreme wrist orientations was examined. This study evinces that individual differences are greater than observed changes in extreme wrist orientations for both propulsion styles and point towards the need for future research on individual differences utilising propulsion styles.